Ecological Momentary Assessments as a Tool to Monitor and Promote the Mediterranean Diet Adherence in the Context of the PENSA Study. (7th June 2021) - Boronat, Anna; Schröder, Helmut; Forcano, Laura; De la Torre, Rafael
Abstract: Objectives: High adherence to the Mediterranean diet (MedDiet) is associated with a risk reduction on cardiovascular and neurodegenerative diseases, cancer and osteoporosis among others. The aim of the present study is to use ecological momentary assessments (EMAs) as a tool to monitor and promote adherence to the MedDiet. Methods: A set of dietary EMAs has been developed aimed at evaluating continuous adherence to the MedDiet. The EMAs are sent daily and enquire about the consumption of 11 key food groups of the Mediterranean diet in the last 24–48 hours in a semi-quantitative way. They have been used to monitor and promote the MedDiet in the frame of a multicomponent life style intervention study which is focused on the prevention of cognitive decline (PENSA study). Participants undergo through a nutritional intervention including individual nutritional sessions and daily EMAs. A total MedDiet adherence score is calculated based on EMAs. Additionally, each food group is monitored individually. On a monthly basis, volunteers receive a personalized feedback including a MedDiet score and its individual components together with recommendations of improvement. Additionally, MedDiet adherence was evaluated at baseline and after 6 months of the intervention using the standardized MEDAS screener. Results: Preliminary results ( n = 11) show that, following 6 months of the intensive nutritional intervention and dietary EMAs, participants increased significantly their adherence to MedDiet (baseline score: 8 (SD = 1.4) vs 6-month score: 10.6 (SD = 0.9); P < 0.001). At baseline, only 2 volunteers met "high adherence" criteria to the MedDiet whereas at the end of the 6 months, 9 volunteers over 11 were categorized into the "high adherence" group. The most important changes observed in MEDAS 6-month score where in the nuts, fruits and vegetable categories; all of them included in the food groups monitored by EMAs. Conclusions: EMAs are a tool to monitor and promote the adherence to the MedDiet. The continuous monitoring of the diet together with the periodic personalized feedbacks send to the volunteers promoted a change in individual's behaviors in favor of the choice of products in line with MedDiet recommendations. Funding Sources: Alzheimer Association, ISCIII FIS and CIBEROBN